Cranial shape variation in jacarean caimanines (Crocodylia, Alligatoroidea) and its implications in the taxonomic status of extinct species: The case of Melanosuchus fisheri. (15th November 2017) - Foth, Christian; Fernandez Blanco, María Victoria; Bona, Paula; Scheyer, Torsten M.
Abstract: Melanosuchus niger (Crocodylia, Alligatoroidea) is one of the six living caimanine species widely distributed throughout the Amazon River basin today. Although there is only one extant species of Melanosuchus, fossil material assigned to this genus, represented by M. fisheri, has been reported from the late Miocene in South America. However, the validity of this taxon has been questioned and a recent investigation indicates that the referred specimen of M. fisheri (MCZ 4336) actually belongs to Globidentosuchus brachyrostris, while those diagnostic characters present in the holotype (MCNC 243) fall into the spectrum of intraspecific variation of M. niger . Here, we compare the skull shape of the holotype of M. fisheri with the ontogenetic series of the four jacarean species ( M. niger, Caiman yacare, Caiman crocodilus, and Caiman latirostris ) using 2D‐geometric morphometric analyses in two different views. The analyses indicate that MCNC 243 falls into the morphospace of M. niger and C. latirostris . Despite strong shape similarities between juveniles of C. latirostris and MCNC 243, further anatomical comparisons reveal notable differences between them. In contrast, no concrete anatomical differences can be found between MCNC 243 and M. niger, although shape analyses indicate that MCNC 243 is relatively robust for its size. Thus, this study is able to confirm that the genus Melanosuchus was present in the late Miocene, but it still remains unclear if MCNC 243 should be treated as a junior synonym or probably a sister species of M. niger . Its Miocene age favors the second option, but as the shape analyses were also not able to extract any diagnostic characters, it should be retained as Melanosuchus cf. niger . Abstract : A comparison of the skull shape of the fossil caiman MCNC 243 with four jacarean caimans indicates that MCNC 243 falls into the morphospace of Melanosuchus niger and Caiman latirostris, while orbit shape and size supports an affiliation with the genus Melanosuchus .